The Effect of Utilizing Kepok Banana Peel on the Sensory Quality of Steamed Sponge Cake as an Alternative Food Product - Fajri, Al; Ishak, Riani Prihatini (YUME : Journal of Management, 2025)
Banana peel waste, especially from the kepok variety, is often discarded despite containing fiber, vitamins, minerals, and antioxidants that are beneficial for health. This study aims to evaluate the potential use of kepok banana peel as an alternative raw material in making steamed sponge cake through organoleptic tests and statistical analysis. This study used an experimental approach with 25 trained and untrained panelists to assess sensory parameters such as color, texture, aroma, and taste. The results showed that steamed sponge cake made from kepok banana peel had a higher level of preference than sponge cake made from kepok banana flesh, especially in the aspects of color (5.84), texture (5.48), and aroma (5.64). These findings indicate that kepok banana peel is worthy of being used as an alternative food ingredient, not only from a technological and nutritional perspective, but also in supporting sustainable consumption practices. This study provides strategic implications for the development of local food products based on organic waste and the empowerment of MSMEs in the food industry.Keywords : Kepok banana peel, steamed cake, organoleptic test, alternative food, sustainability